Comparison of the effectiveness of the "inverted class" method in studying the "Cities of Kazakhstan" module in geography (Journal of Educational Sciences, 2024)
Modern education requires the search for innovative methods that contribute to the active assimilation of knowledge, the development of analytical abilities and increased motivation of students. One such approach is the "inverted class" method. This method is based on the students' preliminary study of the educational material before classes and its in-depth study in the classroom. Research works display the advantages of this strategy in teaching students: they acquire knowledge at a pace convenient for them, get highly developed intellectual efficiency as per Bloom's taxonomy, develop better cooperation, communication skills and skills in the field of software and communication technologies. We present here the efficiency, specific features, advantages and disadvantages of the "inverted class" method when teaching cities. Traditional lectures which teach cities in geography lessons in Kazakhstan do not cover many issues. And the "inverted class" method shows that it provides big opportunities for students to get profound knowledge. That can be proved if to compare students’ knowledge in the experimental and test groups. On completing the experiment all participants filled out questionnaires. The analysis of answers to the questionnairy provided the opportunity to recommend inverted class method in teaching. We applied Likert scale in the results provided by the questionnaire to define students’ sufficiency and effectiveness of learning. Based on the results obtained, recommendations were developed on the use of the "inverted class" method in teaching. Teachers are encouraged to actively use digital resources, plan interactive classes and take into account the level of training of students.Key words: flipped classroom, blended learning, B. Bloom's cognitive levels, critical thinking, the system of knowledge on urban population